FENOMENA BUNUH DIRI DAN HUBUNGANNYA DENGAN TINGKAT PENDIDIKAN DAN JENIS KELAMIN - Sri Wahyuni; Amrazi Zakso; Izhar Salim (Fakultas Keguruan dan Ilmu Pendidikan Universitas Tanjungpura, 2018)
Suicide is a global phenomenon found throughout the region on earth. Suicide is one of the causes of death cases around the world, WHO reveals suicides in Indonesia have fluctuated from year to year. Education influences social roles and division of labor in social life so that someone feels needed in society and this affects the incidence of suicide. In Indonesia suicide often occurs among women both sexual abuse victims and domestic violence victims. The existence of traumatic experiences and feelings of shame towards society are often the main reasons why they often make suicide attempts. Government assistance and the legal umbrella for victims is needed and that is the government’s obligation. However, if the victim is unable to withstand traumatic experience and it becomes a burden of misery in the life of the victim. This paper aims to describe the relationship between the level of education, gender and the phenomenon of suicide.